Biological Effects of Weak Electromagnetic Field on Healthy and Infected Lime (Citrus aurantifolia) Trees with Phytoplasma - Fatemeh Abdollahi; Vahid Niknam; Faezeh Ghanati; Faribors Masroor; Seyyed Nasr Noorbakhsh (The Scientific World Journal)
Exposure to electromagnetic fields (EMF) has become an issue of concern for a great many people and is an active area of research. Phytoplasmas, also known as mycoplasma-like organisms, are wall-less prokaryotes that are pathogens of many plant species throughout the world. Effects of electromagnetic fields on the changes of lipid peroxidation, content of H2O2, proline, protein, and carbohydrates were investigated in leaves of two-year-old trees of lime (Citrus aurantifolia) infected by the Candidatus Phytoplasma aurantifoliae. The healthy and infected plants were discontinuously exposed to a 10 KHz quadratic EMF with maximum power of 9 W for 5 days, each 5 h, at 25°C. Fresh and dry weight of leaves, content of MDA, proline, and protein increased in both healthy and infected plants under electromagnetic fields, compared with those of the control plants. Electromagnetic fields decreased hydrogen peroxide and carbohydrates content in both healthy and infected plants compared to those of the controls.